The Automotive Industry in The European Union, 2014-21 - Sebastian BOBOWSKI; Igor CVECIC; Pawel DOBRZANSKI (Communications of International Proceedings, 2022)
The aim of the article is to provide an overview of the current situation in automotive sector and analysis of main challenges for this industry. For that reason, main statistics for automotive sector in the EU are presented, which confirm importance of this industry in the European economy, as well as in global economy. Also, data about production and trade is analysed. In the last section main challenges for automotive sector are discussed, which are electrification, supply chain localisation, component shortages and vertical integration.
Keywords: Automotive Industry; Competitiveness; Trade.